2019
DOI: 10.1080/1343943x.2019.1698971
|View full text |Cite
|
Sign up to set email alerts
|

Panicle inclination influences pollination stability of rice (Oryza sativa L.)

Abstract: Rice pollination occurs when pollen grains fall by gravity from the anther onto the stigma and has been thought to be assured under suitable conditions. However, the position of the stigma relative to the anther pores may affect pollination. The inclination of panicle, that is quite usual in agricultural scene, may change the relative position of anther and stigma. We investigated the effect of panicle inclination on pollination stability. Pots of rice at flowering stage were tilted at one of the four inclinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…However, we found that small panicle inclination reduced pollination stability in isolated pot-grown rice probably by changing the relative position between anther and stigma, and delaying pollen release (Win et al, 2020). Panicle inclination of 30°increased percentage of florets having less than 10 germinated pollen grains on the stigma after flowering by 24%.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, we found that small panicle inclination reduced pollination stability in isolated pot-grown rice probably by changing the relative position between anther and stigma, and delaying pollen release (Win et al, 2020). Panicle inclination of 30°increased percentage of florets having less than 10 germinated pollen grains on the stigma after flowering by 24%.…”
Section: Introductionmentioning
confidence: 67%
“…From each floret, we randomly selected four anthers to observe at 80× magnification under a digital microscope (KH-7700, Hirox Co., Ltd., Tokyo, Japan). We measured the lengths of dehiscence formed at basal and apical parts of anther (Win et al, 2020).…”
Section: Common Procedures and Data Collection In Experiments 1 Andmentioning
confidence: 99%
“…According to Matsui, Kobayasi, Yoshimoto, Hasegawa, & Tian (2020), strong wind causes the ideal position of the panicle for pollination to decrease. Previously, Win et al (2020a;2020b) noted that pollination success in rice decreased by increasing panicle inclination.…”
Section: Genotype Sensitivity To Heavy Rain and Strong Windmentioning
confidence: 99%
“…In addition, failure of anther dehiscence was also reported to be responsible for low spikelet fertility in drought stressed rice at pre-anthesis stage (Liu et al 2006). Failure of anther dehiscence would certainly prevent stigma from receiving pollen grains for the pollination process (Win et al 2020). Above all, spikelet opening during flowering was a prerequisite for anthesis process to occur in rice (Ekanayake et al 1993).…”
Section: Introductionmentioning
confidence: 99%